Mechanism investigation of α-Ni(OH)2 electrodeposition from a NiCl2 solution. (1st January 2021) - Zhang, Junjie; Zhang, Ting'an; Feng, Sen
Abstract: α-Ni(OH)2 was electrodeposited from NiCl2 solution by membrane electrolysis method. Various ethanol contents and concentration electrolytes were used to investigate the relevant mechanism. XRD and CV results demonstrated a preferentially conducted side reaction of Ni 2+ to Ni. Ethanol was proved to be effective to poison this reaction. Linear relationships of the product mass and electrodeposition time for electrodepositions in 0.1 M NiCl2 solutions indicated an ignored output of Ni. A four-step mechanism for Ni(OH)2 electrodeposition from the side reaction priority system was proposed. XRD and FT-IR results suggested β-Ni(OH)2 and α-Ni(OH)2 were certain to be synthesized in 0.05–0.1 and 0.2–1.0 M NiCl2 solution. β-Ni(OH)2 formed in these low concentration electrolytes was proved to be prevented by circulating the cathodic electrolyte. Analyses suggested β-Ni(OH)2 formed in the present cases might be either converted from α-Ni(OH)2 under high alkaline digestion or synthesized originally due to the proper ratio of Ni 2+ and OH − . Highlights: NiCl2 solution was used for α-Ni(OH)2 electrodeposition. The mechanism of by-product formation and method to prevent were studied. The mechanism of β-Ni(OH)2 formation and method to prevent were analyzed.